Hand Surgery in Thailand - Niempoog, Sunyarn; Witoonchart, Kiat; Jaroenporn, Woraphon (Journal of Hand and Microsurgery, 2021)
Modern hand surgery in Thailand started after the end of World War II. It is divided into 4 phases. In the initial phase (1950-1965), the surgery of the hand was mainly performed by general surgeons. In 1965-1975, which was the second phase, many plastic surgeons and orthopaedic surgeons graduated from foreign countries and came back to Thailand. They played a vital role in the treatment of the surgery of the hand and set up hand units in many centers. They also contributed to the establishment of the “Thai Society for Surgery of the Hand,” which still continues to operate. In the third phase (1975-2000), there was a dramatic development of microsurgery because of the rapid economic expansion. There were many replantation, free tissue transfers, and brachial plexus surgeries in traffic and factory-related accidents. The first hand-fellow training program began in 1993. In the fourth phase (since 2000), the number of hand injuries from factory-related accidents began declining. But the injury from traffic accidents had been increasing both in severity and number. Moreover, the diseases of hand that relate to aging and degeneration had been on the rise. Thai hand surgeons have been using several state-of-the-art technologies such as arthroscopic and endoscopic surgery. They are continuing to invent innovations, generating international publications, and frequently being invited as speakers in foreign countries.
Keywords: hand surgery; microsurgery; Thai; Thailand; history